Conceptualizing and fighting a global insurgency: extraterritorial use of force against jihadist networks in the cases of al Qaeda and the Islamic State - Steinmeir, Dominik (2018)
This thesis seeks to answer the question of how can insur-gent networks of/networked jihadist violent non-state actors be legally conceptualized, what limits are imposed by international and US domestic law on campaigns against such networks, and do those limits allow for effective and legitimate counter-terrorism? It will employ a basic interdisciplinary research de-sign, as defined by Mathias Siems, which uses a legal research question as a starting point, but relies on insights from other disciplines to reach an informed analysis. The thesis will first establish the insurgent nature of ji-hadist groups such as al Qaeda and the Islamic State by taking the claim of their desire to re-establish the Caliphate seriously. It will establish that 'jihadist international relations' — as op-posed to the broader notion of Islamic international relations — divide the world into the dar al-Islam, the world of Islam, and the dar al-harb, the territory of war, which are in a perpetual state of war. It will show that the attempts to pursue this in-surgent aim are increasingly carried out by affiliate organiza-tions. It will then move on to address the gap in the legal litera-ture, which relates to the problem inherent in the United States' 2001 Authorization of Use of Military Force (AUMF), which authorizes the use of force against al Qaeda and increas-ingly groups connected to it, but does not provide a mechanism to legally conceptualize when such groups are covered by the AUMF. It will put forward a legal framework to conceptualize re-lationships between the al Qaeda and Islamic State core groups and their affiliate and associate organizations by drawing on Is-lamic principles of statehood and by drawing an analogy to es-tablished principles on the responsibility of states and interna-tional organizations for wrongful acts. It will argue that affiliate organizations, through offering an oath of allegiance, become de jure members of the overall network and that attribution of their conduct to the overall network should therefore not de-pend on the level of command and control exercised. Actions of associate groups, on the other hand, should only be attributable to such groups if they exercise overall control. The thesis will then move on to investigate the use of force against affiliate organizations under the jus ad bellum, arguing that such of force is possible in self-defence and with the con-sent of the host state. It will establish that states that become the victim of an armed attack can use force if the host states is unable and unwilling to suppress an imminent armed attack by such groups, and that states can, in certain circumstances, rely on the accumulation of events doctrine, provided that such at-tacks are carried out by members of the same network. It will furthermore argue that the jus ad bellum's necessity require-ment should be understood to mandate non-lethal responses, which the thesis refers to as extraterritorial law enforcement, in certain circumstances. The thesis will then move on to the jus in bello. It will reengage with the idea of a "global" armed conflict frequently invoked by the United States. However, the thesis will argue that such conflicts do not encompass the entire globe, but are, in line with the Tadić decision of the International Criminal Tri-bunal for the Former Yugoslavia, limited to the territory under the control of a party to this conflict. It will then draw heavily on US case law to establish when individuals are part of such organizations, and on principles of the law of armed conflict to establish when strikes against those members are lawful. Finally, it will establish the possibility of extraterritorial law enforcement against such organizations, which refers to extra-territorial operations that have the primary aim of apprehend-ing individuals suspected of unlawful activity, or contribute to such operations, for the purpose of criminal prosecution. It will be stablished that such operations are lawful in self-defence for the purpose of preventing an imminent armed attack and that US law does not put up any significant obstacles for prosecuting individuals brought to the United States in such a manner.